2021
DOI: 10.1016/s2213-2600(21)00384-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interferon beta-1a plus remdesivir compared with remdesivir alone in hospitalised adults with COVID-19: a double-blind, randomised, placebo-controlled, phase 3 trial

Abstract: Background Functional impairment of interferon, a natural antiviral component of the immune system, is associated with the pathogenesis and severity of COVID-19. We aimed to compare the efficacy of interferon beta-1a in combination with remdesivir compared with remdesivir alone in hospitalised patients with COVID-19. Methods We did a double-blind, randomised, placebo-controlled trial at 63 hospitals across five countries (Japan, Mexico, Singapore, South Korea, and the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 26 publications
7
125
0
Order By: Relevance
“…Although our genome-wide gene-based association tests did not replicate any findings from a previous pathway-specific study of rare deleterious variants 4 , our results provide robust evidence implicating reduced interferon signalling in susceptibility to critical Covid-19. Importantly, systemic administration of interferon in two large clinical trials, albeit late in disease, did not reduce mortality 31,32 .…”
Section: Discussionmentioning
confidence: 97%
“…Although our genome-wide gene-based association tests did not replicate any findings from a previous pathway-specific study of rare deleterious variants 4 , our results provide robust evidence implicating reduced interferon signalling in susceptibility to critical Covid-19. Importantly, systemic administration of interferon in two large clinical trials, albeit late in disease, did not reduce mortality 31,32 .…”
Section: Discussionmentioning
confidence: 97%
“…Both groups were similar, but contrary to our study, only 6.7% (INF-β) and 6.3% (control) of patients were on ventilation support, and only 33.7% and 34.7% were hospitalized ≥ 2 days. Similarly, a multicenter randomized controlled trial by Kalil et al did not show efficacy of INF-β combined with remdesivir compared to remdesivir alone concerning time to recovery [14] . Patients had mostly mild-to-moderate COVID-19, with only 7% in both groups requiring non-invasive ventilation or high-flow oxygen therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Promising results obtained from three randomized controlled trials with small sample sizes showed that subcutaneous injection of IFN-β in patients with moderate-to-severe COVID-19 improved clinical outcomes with no specific side effects [10] , [11] , [12] . However, two other multicenter randomized controlled trials, mostly in adult inpatients with mild-to-moderate COVID-19, did not show clinical efficacy of interferon treatment [13] , [14] .…”
Section: Introductionmentioning
confidence: 95%
“…In addition, earlier intramuscular administration of IFN-α was suggested to be beneficial for COVID-19 patients (10.2217/fvl-2020-0404). Moreover, differences in biological activity and structure between different type I IFNs may reduce the transcription of ISGs, and eliminate the synergistic effect of the combinational treatment [71]. Therefore, the overall antiviral effect for treatment with IFNs in vivo could be dampened.…”
Section: Discussionmentioning
confidence: 99%